Meningkatkan Keterampilan Proses, Tanggung Jawab, dan Penguasaan Konsep pada Mata Pelajaran Fisika Kelas 10 SMA Lentera Harapan Curug Melalui Penerapan Model Pembelajaran Cycle 7E [Improving Process Skills, Responsibility Attitude, and Mastery Concept in Physics Lesson of Ggrade 10 SMA Lentera Harapan Curug Students Through Learning Model Application Cycle 7E] - Martin Binsartua (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
This research aims to find out the improvement of three learning competencies that are process skills, responsibility attitude, and mastery concept students through learning model application cycle 7E in Physics. The three competencies are very important to be mastered by the students. The research implemented on grade 10 SMA Lentera Harapan Curug students from July to November 2016. The research method is weak experimental design the static-group pretest-posttest. The data obtained using questionnaire and written test to get the mean value and n gain, to see the difference between the experimental class and control class used by Mann Whitney test for process skills and responsibility attitude, and the t-test the mastery concept. The conclusion of Wilcoxon test for process skills, responsibility attitude, and concepts mastery is that there were significant differences in pretest and posttest results of the experimental class by using model 7E cycle learning.